P7 Optimising learning from clinical incidents using in-situ simulation. (5th November 2017) - McCullough, Sarah
Abstract : Background: Learning is a social activity situated within a particular environment or context and takes place through interpersonal interactions with that culture and environment. 1 It is known that the closer the context is to the context of practice, the more effective the learning. 2 It therefore makes logical sense that learning for health care professionals should be undertaken in the workplace. Learning from clinical incidents is integral to maintaining good patient care and safety. In-situ simulation can be used to deliver this learning as it allows the recreation of an incident in the same clinical setting whilst in a safe and controlled environment. Method: A simulation scenario was generated using details from a clinical incident. The following learning objectives were formulated using both the positive and negative issues raised in the root cause analysis: * Recognition, diagnosis and management of hypovolemic shock secondary to concealed blood loss in a newborn. * Knowledge and Implementation of the approach to obtain blood urgently. * Implementation of a multi-disciplinary team approach to management of a neonate born in poor condition requiring resuscitation. The simulation session was then undertaken in similar settings to the clinical incident at two neonatal units. The following were evaluated during the simulation scenario: 1. Demonstration of appropriate adherence to NLS algorithm. 2. Recognition of blood loss being cause of poor condition at birth. 3. Teamwork: a. Atitudes i. Shared belief that everyone works together ii. Sense of collective competence and ability b. Behaviour i. Communication ii. Leadership iii. Mutual Performance monitoring iv. Back up/supportive behaviour v. Mission analysis vi. (Conflict management) c. Cognition i. Accurate and shared mental models 1. Know team structure and roles 2. Awareness of task 3. Situation awareness The debrief was then held using the PEARLS (Promoting Excellence and Reflective Learning in Simulation) format. Results: All of the participants rated the simulation teaching as excellent for relevance, content and presentation. Many also mentioned about how it updated their local knowledge regarding where blood can be obtained urgently. Conclusion: In-situ simulation allows us to review local practices and guidelines and identify those latent errors that are specific to that workplace. The combination of in-situ simulation with learning from incidents can only increase the dissemination and effectiveness of this learning. Regular in-situ simulation can also help to create a culture of safety where there is a constant and active awareness of the potential for things to go wrong. References: . Mann J. Con Ed in the Health Prof 2004;24(S1). . Tocalli-Beller, et al. Int J . Applied Linguistics 2005;15(1). . Brown, et al. Educational Researcher 1989;18(1). . Koens, et al. Medical Education 2005;39(12). . La Rochelle, et al. Medical Education 2011;45(8). . Normal, et al. Medical Education 2012;46(7).